A method to stabilise the performance of negatively fed KM3NeT photomultipliers - Adrián-Martínez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of Instrumentation, 2016)
The KM3NeT research infrastructure, currently under construction in the Mediterranean Sea, will host neutrino telescopes for the identification of neutrino sources in the Universe and for studies of the neutrino mass hierarchy. These telescopes will house hundreds of thousands of photomultiplier tubes that will have to be operated in a stable and reliable fashion. In this context, the stability of the dark counts has been investigated for photomultiplier tubes with negative high voltage on the photocathode and held in insulating support structures made of 3D printed nylon material. Small gaps between the rigid support structure and the photomultiplier tubes in the presence of electric fields can lead to discharges that produce dark count rates that are highly variable. A solution was found by applying the same insulating varnish as used for the high voltage bases directly to the outside of the photomultiplier tubes. This transparent conformal coating provides a convenient and inexpensive method of insulation.
Keywords: Instrument optimization; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (gas) (gas-photocathodes; solid-photocathodes)

A multi-PMT optical module for the IceCube upgrade - Dorn, Christian; Kossatz, M.; Kretzschmann, A.; Ortjohann, H. W.; Reubelt, Jonas; Sulanke, K. H.; Weigel, Robert; Classen, Lew; Kappes, Alexander; Karg, Timo (Proceedings of Science, 2019)
Following the first observation of an astrophysical high-energy neutrino flux with the IceCube Neutrino Observatory in 2013 and the identification of a first cosmic high-energy neutrino source in 2017, the detector will be upgraded with about 700 new advanced optical sensors. This will expand IceCube's capabilities both at low and high neutrino energies. A large fraction of the upgrade modules will be multi-PMT Digital Optical Modules, mDOMs, each featuring 24 three-inch class photomultiplier tubes (PMTs) pointing uniformly in all directions, thereby providing an almost homogeneous angular coverage. The signal from each PMT is digitized individually, providing directional information for the incident photons. Together, the 24 PMTs provide an effective photosensitive area more than twice than that of the current IceCube optical module. The main mDOM design challenges arise from the constraints on the module size and power needed for the 24-channel high-voltage and readout systems. This contribution presents an mDOM design that meets these challenges and discusses the sensitivities expected from these modules.
CRIS-Team Scopus Importer:2021-04-20

Characterisation of the Hamamatsu photomultipliers for the KM3NeT Neutrino Telescope - Aiello, S.; Akrame, S. E.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Baars, M.; et al. (Journal of Instrumentation, 2018)
The Hamamatsu R12199-023-inch photomultiplier tube is the photodetector chosen for the first phase of the KM3NeT neutrino telescope. About 7000 photomultipliers have been characterised for dark count rate, timing spread and spurious pulses. The quantum efficiency, the gain and the peak-to-valley ratio have also been measured for a sub-sample in order to determine parameter values needed as input to numerical simulations of the detector.
Keywords: Cherenkov detectors; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (vacuum)

Characterisation of the Hamamatsu R12199-01 HA MOD photomultiplier tube for low temperature applications - Elorrieta, M. A. Unland; Classen, L.; Reubelt, Jonas; Schmiemann, S.; Schneider, Jonas; Kappes, A. (Journal of Instrumentation, 2019)
We present a detailed characterisation of the new Hamamatsu R12199-01 HA MOD 3-inch photomultiplier tube (PMT) which is under consideration for the use in segmented optical modules of deep-ice neutrino detectors at the South Pole. Because of the significantly lower operation-temperature range compared to standard applications, a focus of our studies lies on the investigation of the temperature dependence of background characteristics (dark count rate, probability of correlated pulses), timing properties, gain and peak-to-valley ratio of this PMT type. In addition, the performance of the "HA coating" intended for background reduction was tested, as well as the influence of conductive objects near the photocathode like reflectors on the PMT noise rate. A low background rate is of particular importance as the deep ice at the South Pole features negligible optical background. We find that the new PMT type is well suited for the intended applications.
CRIS-Team WoS Importer:2019-04-16

Deep sea tests of a prototype of the KM3NeT digital optical module - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; De Asmundis, R.; et al. (European Physical Journal C, 2014)
The first prototype of a photo-detection unit of the future KM3NeT neutrino telescope has been deployed in the deepwaters of the Mediterranean Sea. This digital optical module has a novel design with a very large photocathode area segmented by the use of 31 three inch photomultiplier tubes. It has been integrated in the ANTARES detector for in-situ testing and validation. This paper reports on the first months of data taking and rate measurements. The analysis results highlight the capabilities of the new module design in terms of background suppression and signal recognition. The directionality of the optical module enables the recognition of multiple Cherenkov photons from the same (40)Kdecay and the localisation of bioluminescent activity in the neighbourhood. The single unit can cleanly identify atmospheric muons and provide sensitivity to the muon arrival directions.

Dependence of atmospheric muon flux on seawater depth measured with the first KM3NeT detection units: The KM3NeT Collaboration - Ageron, M.; Aiello, S.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Bagatelas, C.; Barbarino, G.; Baret, B.; et al. (European Physical Journal C: Particles and Fields, 2020)
KM3NeT is a research infrastructure located in the Mediterranean Sea, that will consist of two deep-sea Cherenkov neutrino detectors. With one detector (ARCA), the KM3NeT Collaboration aims at identifying and studying TeV–PeV astrophysical neutrino sources. With the other detector (ORCA), the neutrino mass ordering will be determined by studying GeV-scale atmospheric neutrino oscillations. The first KM3NeT detection units were deployed at the Italian and French sites between 2015 and 2017. In this paper, a description of the detector is presented, together with a summary of the procedures used to calibrate the detector in-situ. Finally, the measurement of the atmospheric muon flux between 2232–3386 m seawater depth is obtained.
CRIS-Team Scopus Importer:2020-02-18

Intrinsic limits on resolutions in muon- and electron-neutrino charged-current events in the KM3NeT/ORCA detector - Adrian-Martinez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of High Energy Physics, 2017)
Studying atmospheric neutrino oscillations in the few-GeV range with a multimegaton detector promises to determine the neutrino mass hierarchy. This is the main science goal pursued by the future KM3NeT/ORCA water Cherenkov detector in the Mediterranean Sea. In this paper, the processes that limit the obtainable resolution in both energy and direction in charged-current neutrino events in the ORCA detector are investigated. These processes include the composition of the hadronic fragmentation products, the subsequent particle propagation and the photon-sampling fraction of the detector. GEANT simulations of neutrino interactions in seawater produced by GENIE are used to study the effects in the 1-20 GeV range. It is found that fluctuations in the hadronic cascade in conjunction with the variation of the inelasticity y are most detrimental to the resolutions. The effect of limited photon sampling in the detector is of significantly less importance. These results will therefore also be applicable to similar detectors/media, such as those in ic
Keywords: Neutrino Detectors and Telescopes (experiments)

KM3NeT front-end and readout electronics system: hardware, firmware, and software - Aiello, Sebastiano; Amllei, Fabrizio; Andre, Michel; Androulakis, Giorgos; Anghinolfi, Marco; Anton, Gisela; Ardid, Miquel; Aublin, Julien; Bagatelas, Christos; Barbarino, Giancarlo; Baret, Bruny; Du Pree, Suzan Basegmez; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2019)
The KM3NeT research infrastructure being built at the bottom of the Mediterranean Sea will host water-Cherenkov telescopes for the detection of cosmic neutrinos. The neutrino telescopes will consist of large volume three-dimensional grids of optical modules to detect the Cherenkov light from charged particles produced by neutrino-induced interactions. Each optical module houses 31 3-in. photomultiplier tubes, instrumentation for calibration of the photomultiplier signal and positioning of the optical module, and all associated electronics boards. By design, the total electrical power consumption of an optical module has been capped at seven Watts. We present an overview of the front-end and readout electronics system inside the optical module, which has been designed for a 1-ns synchronization between the clocks of all optical modules in the grid during a life time of at least 20 years. (C) 2019 Society of Photo-Optical Instrumentation Engineers (SPIE)
CRIS-Team WoS Importer:2020-02-28

Letter of intent for KM3NeT 2.0 - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; et al. (Journal of Physics G: Nuclear and Particle Physics, 2016)
The main objectives of the KM3NeT Collaboration are (i) the discovery and subsequent observation of high-energy neutrino sources in the Universe and (ii) the determination of the mass hierarchy of neutrinos. These objectives are strongly motivated by two recent important discoveries, namely: (1) the high-energy astrophysical neutrino signal reported by IceCube and (2) the sizable contribution of electron neutrinos to the third neutrino mass eigenstate as reported by Daya Bay, Reno and others. To meet these objectives, the KM3NeT Collaboration plans to build a new Research Infrastructure consisting of a network of deep-sea neutrino telescopes in the Mediterranean Sea. A phased and distributed implementation is pursued which maximises the access to regional funds, the availability of human resources and the synergistic opportunities for the Earth and sea sciences community. Three suitable deep-sea sites are selected, namely off-shore Toulon (France), Capo Passero (Sicily, Italy) and Pylos (Peloponnese, Greece). The infrastructure will consist of three so-called building blocks. A building block comprises 115 strings, each string comprises 18 optical modules and each optical module comprises 31 photo-multiplier tubes. Each building block thus constitutes a three-dimensional array of photo sensors that can be used to detect the Cherenkov light produced by relativistic particles emerging from neutrino interactions. Two building blocks will be sparsely configured to fully explore the IceCube signal with similar instrumented volume, different methodology, improved resolution and complementary field of view, including the galactic plane. One building block will be densely configured to precisely measure atmospheric neutrino oscillations.
Keywords: deep sea neutrino telescope; neutrino astronomy; neutrino mass hierarchy; neutrino physics

PMT characterisation for the KM3NeT project - Herold, Björn; Kalekin, Oleg; Reubelt, Jonas (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
Keywords: Cherenkov light; KM3NeT; High energy neutrino detection; Photomultiplier

Sensitivity of the KM3NeT/ARCA neutrino telescope to point-like neutrino sources - Aiello, S.; Akrame, S. E.; Ameli, F.; G. Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Bagatelas, C.; et al. (Astroparticle Physics, 2019)
KM3NeT will be a network of deep-sea neutrino telescopes in the Mediterranean Sea. The KM3NeT/ARCA detector, to be installed at the Capo Passero site (Italy), is optimised for the detection of high-energy neutrinos of cosmic origin. Thanks to its geographical location on the Northern hemisphere, KM3NeT/ARCA can observe upgoing neutrinos from most of the Galactic Plane, including the Galactic Centre. Given its effective area and excellent pointing resolution, KM3NeT/ARCA will measure or significantly constrain the neutrino flux from potential astrophysical neutrino sources. At the same time, it will test flux predictions based on gamma-ray measurements and the assumption that the gamma-ray flux is of hadronic origin. Assuming this scenario, discovery potentials and sensitivities for a selected list of Galactic sources and to generic point sources with an E −2 spectrum are presented. These spectra are assumed to be time independent. The results indicate that an observation with 3σ significance is possible in about six years of operation for the most intense sources, such as Supernovae Remnants RX J1713.7-3946 and Vela Jr. If no signal will be found during this time, the fraction of the gamma-ray flux coming from hadronic processes can be constrained to be below 50% for these two objects.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Astrophysical neutrino sources; Cherenkov underwater neutrino telescope; KM3NeT

The prototype detection unit of the KM3NeT detector: KM3NeT Collaboration - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Androulakis, G. C.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, M.; et al. (European Physical Journal C: Particles and Fields, 2016)
A prototype detection unit of the KM3NeT deep-sea neutrino telescope has been installed at 3500m depth 80 km offshore the Italian coast. KM3NeT in its final configuration will contain several hundreds of detection units. Each detection unit is a mechanical structure anchored to the sea floor, held vertical by a submerged buoy and supporting optical modules for the detection of Cherenkov light emitted by charged secondary particles emerging from neutrino interactions. This prototype string implements three optical modules with 31 photomultiplier tubes each. These optical modules were developed by the KM3NeT Collaboration to enhance the detection capability of neutrino interactions. The prototype detection unit was operated since its deployment in May 2014 until its decommissioning in July 2015. Reconstruction of the particle trajectories from the data requires a nanosecond accuracy in the time calibration. A procedure for relative time calibration of the photomultiplier tubes contained in each optical module is described. This procedure is based on the measured coincidences produced in the sea by the ^4040K background light and can easily be expanded to a detector with several thousands of optical modules. The time offsets between the different optical modules are obtained using LED nanobeacons mounted inside them. A set of data corresponding to 600 h of livetime was analysed. The results show good agreement with Monte Carlo simulations of the expected optical background and the signal from atmospheric muons. An almost background-free sample of muons was selected by filtering the time correlated signals on all the three optical modules. The zenith angle of the selected muons was reconstructed with a precision of about 3^° ∘.